Estados ligados de um sistema quântico de três de corpos em duas dimensões na aproximação Born-Oppenheimer - Rosa, Derick dos Santos [UNESP] (2016)
In this thesis we study mass-imbalanced three-body system in two dimensions using BornOppenheimer approximation. Considering the heavy-light particle system interacting through zero-range interaction and disregarding interaction between the heavy-heavy, we study effects the angular momentum and mass ratio difference. Decreasing the mass difference between the heavy and the light particles a smaller number of bound states is found. Increasing the angular momentum we add to the system a repulsive potential, making the system weakly bounded, in this case a small number of bound states are expected. Considering a gaussian potential between the heavy-heavy particles it is possible to unbounded the system and observe tunneling phenomena. The considerable change in the tunneling region for the mean square radii indicates an increase in the system size, making this region interesting to be experimentally detected.